2021
DOI: 10.17245/jdapm.2021.21.6.565
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of transcutaneous electrical nerve stimulation as an adjunct therapy in trigeminal neuralgia - a randomized double-blind placebo-controlled clinical study

Abstract: Background Trigeminal neuralgia (TN) is a severe form of pain that affects the daily activities of a patient. Transcutaneous electrical nerve stimulation (TENS) therapy is an emerging option for the treatment of acute and chronic pain. The aim of this study was to evaluate the effect of TENS therapy as an adjunct to drug therapy for the treatment of TN. Methods A total of 52 patients diagnosed with TN according to the International Classification of Headache Disorders (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…of migraine days nt Jiang et al [ 42 ] 165 31 ± 11 Open-label, parallel, RCT 60 Hz eTNS + FLZ vs FLZ 91 20 Day 16 No. of migraine days, % responder rate, migraine pain intensity; medication intake nt Trigeminal Neuralgia Bisla et al [ 71 ] 52 56 ± nr Double-blind, parallel, RCT 100 Hz eTNS + CBZ vs sham eTNS + CBZ 12 20 Day nr Pain intensity, pain impact on everyday functioning nt Yameen et al [ 72 ] 31 50 ± 11 Open-label, parallel, non-RCT Constant v Theta-Burst 250 Hz eTNS nr 30 Day nr Pain intensity nt ADHD-RS Attention-Deficit/Hyperactivity Disorder Rating Scale, ANT Attention Network Task, BAI Beck Anxiety Inventory, BDI Beck Depression Inventory, CBZ Carbamazepine, CDI Children’s Depression Inventory, CDRS-Revised Children’s Depression Rating Scale, CGI Conners Global Index, CGI-I Conners Global Index Investigator-Rated, CGI-S Conners Global Index Self-Rated, CSHQ Children’s Sleep Habits Questionnaire, C-SSRS Columbia Suicide Severity Rating Scales, DHI Dizziness Handicap Inventory, ELDQOL Epilepsy and Learning Disabilities Quality of Life Scale, ESS Epworth Sleepiness Scale, eTNS external trigeminal nerve stimulation, FLZ Flurazine, GCI-I Global Clinical Impression-Investigator Rated, HARS Hamilton Anxiety Rating Scale, HDRS Hamilton Depression Rating Scale, HIT Headache Impact Test, HRSD Hamilton Rating Scale for Depression, Hz Frequency, IES-R Impact of Event Scale — Revised, ISI Insomnia Severity Index, LSSS Liverpool Seizure Severity Scale, MASC Multidimensional Anxiety Scale for Children, MOCA Montreal Cognitive Assessment, NDP Nimodipine, NM Nimesulide, nr not reported, nt not tested, PCL-C Post-Traumatic Stress Disorder (PTSD) Check List Scale, PSS Pittsburgh Sleep Scale, PSQI Pittsburgh sleep quality index, RBZ Rizatriptan, RCT randomized controlled trial, SDMST Sternberg delayed match to sample task, SF-36 Short Form Health Survey, SWMT Spat...…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…of migraine days nt Jiang et al [ 42 ] 165 31 ± 11 Open-label, parallel, RCT 60 Hz eTNS + FLZ vs FLZ 91 20 Day 16 No. of migraine days, % responder rate, migraine pain intensity; medication intake nt Trigeminal Neuralgia Bisla et al [ 71 ] 52 56 ± nr Double-blind, parallel, RCT 100 Hz eTNS + CBZ vs sham eTNS + CBZ 12 20 Day nr Pain intensity, pain impact on everyday functioning nt Yameen et al [ 72 ] 31 50 ± 11 Open-label, parallel, non-RCT Constant v Theta-Burst 250 Hz eTNS nr 30 Day nr Pain intensity nt ADHD-RS Attention-Deficit/Hyperactivity Disorder Rating Scale, ANT Attention Network Task, BAI Beck Anxiety Inventory, BDI Beck Depression Inventory, CBZ Carbamazepine, CDI Children’s Depression Inventory, CDRS-Revised Children’s Depression Rating Scale, CGI Conners Global Index, CGI-I Conners Global Index Investigator-Rated, CGI-S Conners Global Index Self-Rated, CSHQ Children’s Sleep Habits Questionnaire, C-SSRS Columbia Suicide Severity Rating Scales, DHI Dizziness Handicap Inventory, ELDQOL Epilepsy and Learning Disabilities Quality of Life Scale, ESS Epworth Sleepiness Scale, eTNS external trigeminal nerve stimulation, FLZ Flurazine, GCI-I Global Clinical Impression-Investigator Rated, HARS Hamilton Anxiety Rating Scale, HDRS Hamilton Depression Rating Scale, HIT Headache Impact Test, HRSD Hamilton Rating Scale for Depression, Hz Frequency, IES-R Impact of Event Scale — Revised, ISI Insomnia Severity Index, LSSS Liverpool Seizure Severity Scale, MASC Multidimensional Anxiety Scale for Children, MOCA Montreal Cognitive Assessment, NDP Nimodipine, NM Nimesulide, nr not reported, nt not tested, PCL-C Post-Traumatic Stress Disorder (PTSD) Check List Scale, PSS Pittsburgh Sleep Scale, PSQI Pittsburgh sleep quality index, RBZ Rizatriptan, RCT randomized controlled trial, SDMST Sternberg delayed match to sample task, SF-36 Short Form Health Survey, SWMT Spat...…”
Section: Resultsmentioning
confidence: 99%
“…The mean dose of carbamazepine prescribed to participants was significantly reduced immediately, 6-weeks, 12-weeks, but not 3-months, after real stimulation compared to sham, while pain intensity and its effect on everyday functioning remained unchanged. No group-by-time interaction was conducted [ 71 ]. One parallel-arm, unblinded head-to-head trial ( N = 31 adults with trigeminal neuralgia) reported improvement in pain intensity with constant or theta-burst eTNS, for 3 weeks, but without statistical analyses [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations